Temporal variation in nutritional status and preoperative anemia among patients with retroperitoneal soft tissue sarcoma: a retrospective longitudinal cohort study - Willis, Franziska; Trunk, Anna-Marlen; Musa, Julian; Harnoß, Jonathan M.; Strowitzki, Moritz; Engerer, Cosima; Harnoß, Julian-Camill; Saeedi, Mohammed al; Büchler, Markus W.; Schneider, Martin (Langenbeck's archives of surgery, 2025)
Optimal management of retroperitoneal soft tissue sarcoma (RPS) often requires extensive tumor resections, frequently involving gastrointestinal organs. The impact of these procedures on the nutritional status and hemoglobin (Hb) levels of RPS patients remain unexplored. In this study, we aimed to evaluate preoperative nutritional status as well as the prevalence of anemia in RPS patients, and to investigate longitudinal changes throughout the disease course in order to identify potential strategies for prehabilitation.